2010
DOI: 10.1152/ajpcell.00461.2009
|View full text |Cite
|
Sign up to set email alerts
|

A preferential p110α/γ PI3K inhibitor attenuates experimental inflammation by suppressing the production of proinflammatory mediators in a NF-κB-dependent manner

Abstract: MR.A preferential p110␣/␥ PI3K inhibitor attenuates experimental inflammation by suppressing the production of proinflammatory mediators in a NF-Bdependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 56 publications
3
32
0
1
Order By: Relevance
“…Cytokine Expression-In addition to the role played by STAT1 and STAT3, we investigated whether NF-B, a transcription factor commonly associated with cytokine regulation (17)(18)(19)(20)(21), was induced by IL-27 in monocytic cells. THP-1 cells were treated with IL-27 for times ranging from 5-120 min, followed by Western blot analysis for phosphorylated NF-B p50 subunit (p-NF-B p50) (Fig.…”
Section: Inhibition Of Nf-b Dna Binding Activity Blocks Il-27-inducedmentioning
confidence: 99%
“…Cytokine Expression-In addition to the role played by STAT1 and STAT3, we investigated whether NF-B, a transcription factor commonly associated with cytokine regulation (17)(18)(19)(20)(21), was induced by IL-27 in monocytic cells. THP-1 cells were treated with IL-27 for times ranging from 5-120 min, followed by Western blot analysis for phosphorylated NF-B p50 subunit (p-NF-B p50) (Fig.…”
Section: Inhibition Of Nf-b Dna Binding Activity Blocks Il-27-inducedmentioning
confidence: 99%
“…The PIK-75 treatment was well tolerated, and normal numbers and percentages of the main lymphocyte populations were observed 20 days after termination. Previous results have also shown that PIK-75 inhibits secretion of inflammatory cytokines in cells from patients with active rheumatoid arthritis (14). This suggested that PIK-75 might be useful as a therapeutic agent in arthritis.…”
Section: Discussionmentioning
confidence: 76%
“…In contrast, using PIK-75, we have observed strong effects on activated or resting T cells at ten-fold lower concentrations (::::0.1~M), and clear effects on cytokine secretion or proliferation using concentrations as low as 0.01~M PIK-75. These differences among inhibitors are not likely due to differences in their p 11 Oa IC so [0.006 and 0.032 mM, respectively, for PIK-75 and A66 (19)], and seem specific for lymphocytes, as an IC so 2:20 mM for PIK-75 toxicity in monocytes and synovia have been reported (14). Inhibition of other Class I PI3-K isoforms might be involved as the IC so of PIK-75 is relatively low (0.080, 0.164 and 0.033 mM for p110~, p1100 and pi lOy, respectively) (19).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations